Economic sanctions and trade flows in the neighbourhood - Vincenzo Bove; Jessica Di Salvatore; Roberto Nisticò (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We investigate the effect of economic sanctions on trade flows in countries sharing a border with the sanctioned state. On the one hand, trade models suggest that trade flows should decrease as sanctions disrupt trading routes and economic ties with suppliers and customers. On the other hand, countries can circumvent trade restrictions by clandestinely exchanging goods with sanctioned countries across the border and trading on its behalf. If this is the case, we should expect an increase in their imports and/or exports. To address this issue, we combine large-N panel data analysis and comparative case-study analysis using the synthetic control method. We find that, on average, economic sanctions tend to have a negative effect on trade patterns. Yet, case studies reveal a significant degree of heterogeneity in countries' responses. We present several cases where we detect a substantial increase in trade flows when land neighbours are targeted with economic sanctions.
Keywords: F14; F51; F53; P16; 330; economic sanctions; trade; land neighbours; synthetic control method